2019
DOI: 10.1021/acs.jchemed.8b00920
|View full text |Cite
|
Sign up to set email alerts
|

Designing ColorX, Image Processing Software for Colorimetric Determination of Concentration, To Facilitate Students’ Investigation of Analytical Chemistry Concepts Using Digital Imaging Technology

Abstract: This work combines laboratory quantitative analysis of colored solutions and common devices for digital imaging (digital or web cameras or mobile phones, i.e., smartphones). ColorX software, specially designed for this study, was used for data collection and analysis in order to calculate concentrations of colored solutions from measured RGB values. Three different custom methods for determination of concentration have been developed: (i) RGB value measurement by pixel, (ii) RGB value measurement by pixel and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 31 publications
0
30
0
Order By: Relevance
“…There are several ways to measure R, G, and B intensities using mobile phone applications and software. ,,, In this study, R, G, and B intensities in the photographs were measured using ImageJ . A detailed description of how R, G, and B intensities were calculated is given in the Supporting InformationExperimental Details, Image Processing.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There are several ways to measure R, G, and B intensities using mobile phone applications and software. ,,, In this study, R, G, and B intensities in the photographs were measured using ImageJ . A detailed description of how R, G, and B intensities were calculated is given in the Supporting InformationExperimental Details, Image Processing.…”
Section: Resultsmentioning
confidence: 99%
“…As a result, smartphones are promising tools for use in field analysis in remote regions and developing countries. , In education research, there have been numerous reports using smartphone cameras in chemical analysis. Some examples include for titration end-point determination, , in colorimetric studies of chemical kinetics, for measuring contact angle, for paper-based colorimetric microfluidic devices, and as a detector component in 3D printed spectrophotometers. , Kuntzleman et al and Knutson and Jacobson have shown that RGB image analysis of chromophore-containing samples photographed with an irradiant background (in their examples, colored and white PowerPoint slides, respectively) can be used as a visible-light spectrophotometer. , In this example, spectral analysis is limited to red, green, and blue channelsthus, the method presumably works best with chromophores that absorb purely red, green, or blue wavelengths. Given that most college students have access to or possess a smartphone or digital camera, colorimetric and absorbance-based smartphone analyses are well-suited for chemistry experimentation at home.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, recently researchers reported a smartphone-based colorimetry process that can be used for similar quantification. 17,18 This setup can be prepared in the laboratory, which is convenient and inexpensive, too. A schematic representation of smartphone-based colorimetry is shown in Figure 5.…”
Section: ■ Demonstration and Observationsmentioning
confidence: 99%
“…The number of molecules (n X =n NO2 ) can be determined with the Griess-Saltzman reagent, which reacts with NO 2 to form a purple azo product (Saltzman 1954). In the last decade, new measurement techniques employing digital image-based (DIB) procedures have been reported for color determination (da Silva and Borges 2019; Kiliç et al 2018;Moraes et al 2014;Passaretti Filho et al 2015;Ravazzi et al 2018;Šafranko et al 2018). The technique was recently used to speed up the determination of ozone with a passive sampler (Cerrato-Alvarez et al 2020;Garcia et al 2014).…”
Section: Introductionmentioning
confidence: 99%